Anti-diabetic effect of coffee on alloxan induced diabetic rats / Nurfarhana Muhamad Hakimi - Muhamad Hakimi, Nurfarhana (Faculty Of Applied Sciences, 2017)
Coffee is widely known as the antioxidant reagent that helping people in reducing sleepiness. Nevertheless, the chemical components in coffee are also in reducing the blood glucose level of diabetic infected organism which not very well known yet. This is study is on purpose to indicate and prove that the coffee are having an abilities in reducing the blood glucose level and body weight of the Alloxan induced diabetic rats. Out of 5 samples of diabetic rats are used, the administration of coffee treatment showed the positive result on final reading in decreasing blood glucose level and body weight. For the negative control which is the rat are treated with only distilled water are showing the negative result on final reading which indicating the increasing in reading of blood glucose level and body weight of the rats. For the positive control of the experiment, which the rat are treated using metformin, the result is showing the positive result in lowering blood glucose level and body weight on final reading. In focus of finding the best concentration of coffee that can lowering blood glucose level was in 20% of coffee concentration from a reading 11.8 mmol/dL to 5.3 mmol/dL while for lowering body weight 30% of coffee concentration showing the best reading by lowering 232.19 gram to 215.76 gram. Thus, the coffees are having the mechanism that can lower the blood glucose and body weight of diabetic rats.